Factorizations of Möbius gyrogroups - Ferreira, Milton (2009)
In this paper, we consider a Möbius gyrogroup on a real Hilbert space (of finite or infinite dimension) and we obtain its factorization by gyrosubgroups and subgroups. It is shown that there is a duality relation between the quotient spaces and the orbits obtained. As an example, we present the factorization of the Möbius gyrogroup of the unit ball in R^n linked to the proper Lorentz group Spin+(1, n).